Assessing the Functional Capacity of the Knee Joint Among Boys and Girls Suffering Anterior Cruciate Ligament (ACL) Injuries - Del Bel, Michael Joseph (Université d'Ottawa / University of Ottawa, 2023)
Despite the well-researched impact of ACL injuries, both acutely and longitudinally, and even though adolescent females have the highest risk of sustaining an ACL injury, there is surprisingly very little biomechanical research conducted on adolescent populations after an ACL rupture has taken place. The increasing rates of ACL injuries and re-injury among adolescents demonstrates a need for improved rehabilitation and return-to-activity (RTA) guidelines that are age/maturity- and sex-appropriate. To accomplish this, the first step is to describe this population alongside a non-injured activity-, maturity- and sex-matched population. Therefore, the overall purpose of this Doctoral thesis was to provide evidence to support the creation of return-to-activity guidelines for adolescent patients with ACL injuries. The findings of this thesis, briefly outlined below, can directly contribute to improving clinical and rehabilitation management of ACL injuries among adolescent males and females. First, a systematic review was performed to synthesize sex differences in muscle activation patterns in movements associated with ACL injuries in both adult and adolescent populations. Ultimately, 30 articles were included in the review with a wide range of inconsistent findings. In brief, females demonstrated higher pre- and post-landing activation of the quadriceps and lower activation of the hamstrings in 15 of 27 studies. Females also had higher quadriceps-to-hamstring co-contraction ratios during pre- and post-landing phases compared to their male counterparts in 4 of 9 studies. What's more concerning was the identification of only five research articles that evaluated muscle activations in adolescent or younger cohorts, further emphasising the importance of addressing this gap in literature. The second article of this thesis explored metrics used to evaluate knee joint function that are often a part of rehabilitation guidelines, such as limb symmetry indices (LSI) during single limb hopping and strength tasks. To date, no evidence exists to support or refute the use of these measures in an adolescent population. Therefore, we sought to investigate LSIs and knee joint function among adolescent males and females with and without ACL-injuries during single-limb assessments. A total of 141 participants were recruited and evaluated during a series of maximum voluntary tasks; isometric knee extension and flexion, and single-limb hopping tasks (anterior-hops, lateral-hops, 6m timed-hops, cross-hops, and triple-hops). In brief, females and males with ACL injuries had lower performance metrics compared to their matched controls, however, the differences were not the same within each sex. Females displayed deficits in all tasks, whereas males with and without ACL injuries were only different in the anterior-hop, triple-hop, and knee extension tasks. The final two articles of this thesis are complimentary as they both explored knee stabilisation strategies during countermovement jumps (CMJs) and side-cutting tasks. However, Article 3 included only adolescent males and females without ACL injuries to identify the influence of sex and limb-dominance on knee stabilisation strategies, whereas Article 4 included the same uninjured cohorts but compared with matched groups of males and females with ACL injuries. In both studies, surface electromyography and full-body kinematics were captured during CMJs and side-cutting. Knee stabilisation strategies were evaluated using co-activation indices (CIs), full muscle waveforms, knee joint flexion stiffness (KJFS) and knee joint sagittal and frontal excursions (KJSE and KJFE, respectively). In Article 3, sex differences were observed in CIs, with females having higher medial CIs in the non-dominant limb in both CMJs and side-cuts, and higher total CIs in the non-dominant limb during side-cuts. Between-limb differences were present in both sexes. Females had higher total CI in their non-dominant limb in CMJs and higher frontal KJE in their non-dominant limb during the stance phase of side-cuts. Males had higher medial CIs in their dominant limb in CMJs and higher sagittal KJE in their non-dominant limb during the preparatory and landing phases of CMJs. No significant sex or limb differences were identified in individual muscle activations or KJFS. Based on these findings, males and females were treated statistically independent when evaluating the effect of ACL-injury in Article 4. Interestingly, when comparing groups, only one significant effect of injury was observed in knee stability metrics; males with ACL injuries had significantly higher vastus medialis activity during the preparatory phase of the CMJ compared to their uninjured counterparts. There were no other significant differences in either task. Despite the importance of ACL injury prevention in adolescents, the evidence on sex difference in muscle activation patterns in this population is still scarce. The results of this Doctoral thesis indicate that males and females in adolescent populations have differences in knee stabilisation strategies and overall knee joint function. These findings further support the need for additional research considering risk factors such as, age/maturity-, sex-, and limb-dominance. This research will contribute to the tailoring of rehabilitation programs, thus providing an opportunity to improve the success rate of rehabilitation following ACL-injury among adolescents.
Keywords: anterior cruciate ligament injuries; sex differences; adolescents; knee stability